Graphic representation of temporality in vegetation species manuals (ARQUISUR Revista, 2021)
Whether we are talking about a landscape, architecture or urban planning project, plants are one of the main components in the design of outdoor spaces. The incorporation of plants in a proposal implies projecting with a living material, whose morphology and appearance change substantially over time. This article presents a research project that analyzes the graphics used in a series of popular publications or manuals on plant species. These publications were mainly aimed at architects and were made by the Design Institute (IDD) of the Faculty of Architecture (FADU) between 1963 and 1993. For this, the way in which the graphic resources adopted in the illustrations of different plant species allow the time dimension to be considered.
Keywords: coding; graphic expression; manuals; landscape; project